2020
DOI: 10.1136/esmoopen-2019-000635
|View full text |Cite
|
Sign up to set email alerts
|

223-Radium for metastatic osteosarcoma: combination therapy with other agents and external beam radiotherapy

Abstract: BackgroundBone-seeking radiopharmaceuticals can deposit radiation selectively to some osteosarcoma tumours because of the bone-forming nature of this cancer.ObjectivesThis is the first report of using 223-radium, an alpha-emitting calcium analogue with a high therapeutic index, in combination therapy with other agents in 15 patients with metastatic osteoblastic osteosarcoma.MethodsCandidates for alpha-radiotherapy if 99mTc-MDP bone scan had avid bone-forming lesions and no therapy of higher priority (eg, defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…Beyond ifosfamide and etoposide, the rational selection of agents to further modify adjuvant chemotherapy remains difficult. There are limited active treatments for patients with metastatic disease, including ifosfamide-etoposide (IE) [ 44 ], single agent ifosfamide [ 40 , 42 , 43 ], regorafenib [ 45 ], gemcitabine-docetaxel [ 46 ], cabozantinib [ 47 ], pazopanib [ 48 ] ± SBRT [ 49 ] and radium-223 alone or in combination [ 50 , 51 ]. Given the modest response rates to therapies beyond ifosfamide ± etoposide, a thoughtful, likely translational, approach is needed to identify new therapies with a high likelihood of success.…”
Section: Tailoring Treatment For Patients With Poor Pathological Rmentioning
confidence: 99%
“…Beyond ifosfamide and etoposide, the rational selection of agents to further modify adjuvant chemotherapy remains difficult. There are limited active treatments for patients with metastatic disease, including ifosfamide-etoposide (IE) [ 44 ], single agent ifosfamide [ 40 , 42 , 43 ], regorafenib [ 45 ], gemcitabine-docetaxel [ 46 ], cabozantinib [ 47 ], pazopanib [ 48 ] ± SBRT [ 49 ] and radium-223 alone or in combination [ 50 , 51 ]. Given the modest response rates to therapies beyond ifosfamide ± etoposide, a thoughtful, likely translational, approach is needed to identify new therapies with a high likelihood of success.…”
Section: Tailoring Treatment For Patients With Poor Pathological Rmentioning
confidence: 99%
“…Radiotherapy is effective in some of the selected osteosarcoma patients. In addition, alpha emitter radium-223 can be a new radiation option for metastatic osteosarcoma but is just reported in some clinical cases [25,26]. It still takes a long time to develop radiotherapy to generally improve the survival of osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a long-term follow-up study of the same patient cohort, the authors reported disease stabilisation in seven of the 10 patients, with a median progression-free survival of 107.7 months (range 47.2e111.4 months) versus 26.2 months (range 13.8e75.9 months) for patients with meningioma progression [63]. Anderson et al [64] reported the first use of radium-223 for osteoblastic bone metastases from osteosarcoma in a series of 15 patients. As well as radium-223 (55.13 kBq/kg per cycle, up to six cycles), 12 patients received stereotactic body radiotherapy (SBRT; mean dose, 40 Gy in five fractions) or other EBRT (45 Gy in 15 fractions) either concurrently, concurrently and sequentially or sequentially.…”
Section: Clinical Experience Of External Beam Radiotherapy Plus Molecular Radiotherapy Combination Protocolsmentioning
confidence: 93%